Suppressive Activity of Pemirolast Potassium, an Antiallergic Drug, on Glomerulonephritis - Gohda, Tomohito; Ra, Chisei; Hamada, Chieko; Tsuge, Toshinao; Kawachi, Hiroshi; Tomino, Yasuhiko (Arzneimittelforschung, 2008)
It is still difficult to manage chronic glomerulonephritis with corticosteroids because of safety concerns, especially for patients with mild symptoms and infants. Therefore, an alternative approach is greatly required. Pemirolast potassium (CAS 100299-08-9) is an antiallergic drug with high safety.Two glomerulonephritis rat models were prepared to examine the pharmacological actions of pemirolast potassium: one reversible model prepared with the anti-Thy-1 antibody, and another irreversible model by unilateral nephrectomy and with the anti-Thy-1 antibody. Pemirolast potassium was administered to 10 Japanese chronic glomerulonephritis patients concurrently affected by allergic rhinitis in order to examine its efficacy for mild proteinuria.Pemirolast potassium 1 and 10 mg/kg markedly inhibited proteinuria in the reversible model. In the irreversible model, pemirolast potassium 3 mg/kg showed a significant decrease in the incidence of glomerulosclerosis. In chronic glomerulonephritis patients, pemirolast potassium, 10 mg twice daily, for 6 months, significantly reduced the severity of proteinuria.Our research suggested the efficacy of pemirolast potassium in glomerulonephritis. A well-controlled study is considered necessary to validate pemirolast potassium as a therapeutic drug for glomerulonephritis.
Keywords: Alegysal®; Antiallergic drugs; CAS 100299-08-9; Glomerulonephritis, anti-Thy-1 antibody, experimental; Pemirolast potassium, efficacy in glomerulonephritis; Steroids